PERANCANGAN SISTEM ABSENSI KEHADIRAN KARYAWAN MENGGUNAKAN BARCODE BERBASIS CLIENT SERVER - Budi Santoso; Triyanto Triyanto (Lembaga Pengembangan Kinerja Dosen, 2022)
The attendance system aims to make it easier in terms of employee attendance at the office and this system uses visual basic software. The problem why you have to use this system is because the employee attendance method still uses the manual method so that it cannot be effective and efficient at work. The advantage that can be obtained by using this system is that it can make it easier for employees in terms of attendance at the office by using computer facilities using barcodes. The benefits provided to the company are to simplify and speed up the work of employees so that they can improve employee discipline at the company PT. Priorit